INFLUENCE OF ENTERAL PARASITES ON THE BLOOD VITAMIN-A LEVELS IN PRESCHOOL-CHILDREN ORALLY SUPPLEMENTED WITH RETINOL AND OR ZINC - Marinho, H. A.; Shrimpton, R.; Giugliano, R.; Burini, Roberto Carlos [UNESP] (Stockton Press, 1991)
A sample of 471 pre-school children who frequented schools and creches in a poor district of Manaus (Amazonas), Brazil, were randomly submitted to faecal parasitological tests. Two-hundred-and-forty children from both sexes between the ages of 3 and 7 years with Ascaris lumbricoides and/or Giardia lamblia were selected. The objective of the study was to determine the possible influence of these two intestinal parasites and vitamin A and/or zinc supplementation on the serum retinol levels of primary school children. The children were submitted to clinical and anthropometric examinations, dietary interviews and biochemical examinations of retinol and carotene in the serum and of zinc in the hair. The parasitic incidence was 85.0% and about 54% of the children were polyparasitic. During the pretreatment phase, the retinol and carotene serum levels were 36% and 57%, respectively, below the normal levels. Using the Waterlow classification, the anthropometric analyses revealed that 88% of the children showed normal growth. A significant effect was observed of the anti-parasitic medicine on the serum retinol levels.